The lack of genotoxic activity of antitumor drug paclitaxel in lymphocytes exposed in vitro to therapeutic drug concentrations - Maria Górecka, Karolina; Szyfter, Krzysztof; Gawęcki, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2003)
Paclitaxel is an anticancer drug used in the treatment of ovarian cancer, breast cancer, non small lung cancer and Kaposi’s sarcoma (connected with HIV) with very good results. It can be also used in combination with other drugs. There are reported studies of paclitaxel in the treatment of other cancers, including, for example, head and neck cancer, where paclitaxel was used as a sensitiser in radiotherapy. Paclitaxel, in contrast to other drugs interacting with DNA and causing DNA lesions, binds to microtubules. Then a cell becomes blocked during the G2/M phases of the cell cycle, forming a hyperstable mitotic spindle and cannot divide. However, it has been suggested that paclitaxel could act in cells also in other ways. Hence, a question of genotoxic activity of paclitaxel emerges. In this study the comet assay was used to estimate genotoxity, and the apoptosis test to check whether the drug is active in the cells. The experiments were conducted on blood of healthy volunteers: 35 for the comet assay, and 5 for the apoptosis. Paclitaxel was used in therapeutic concentrations. The obtained results suggest that paclitaxel does not induce damage to DNA, although it is active in cells, and causes apoptosis. Thus, the results suggest that paclitaxel does not interact with not resting cells and is safe for patients.